Effect of mass recovery evaporator temperature and condenser temperature on the performance of a solar adsorption-based desalination plant. Issue 2 (17th February 2019) - Logesh, K.; Subesh, T.; Aravindh Raj, B. R.; Arunkumar, K.
ABSTRACT: Water scarcity increases alarmingly as the population increases. Over the years, a number of salt water desalination techniques have been proposed and reached limitations. The requirement of minimum energy is very well satisfied by an adsorption system, since it can operate with low-grade energy and waste heat exhaust from most industries. The first part of this work discusses the effect of condenser and evaporator temperatures on the performance of silica-gel adsorption cycle mathematically. The second part discusses the performance variations due to mass recovery in the two-bed adsorption system mathematically. It was found that the reduction in condenser temperature and increase in the evaporator temperature both increase the fresh water productivity and cooling capacity of a plant. A desalination plant with mass recovery assistance is superior in performance than the conventional plant. Portable water productivity of 8 m 3 /day/ton is achieved with the condenser temperature of 15°C and the evaporator temperature of 30°C.